Estimation of carrier and channel parameters in time‐selective fading channels. Issue 12 (1st August 2015) - Gappmair, Wilfried; Bergmann, Michael
Abstract : Assuming a land‐mobile satellite link with negligible multipath and shadowing effects, the corresponding channel model is adequately described by a correlated Rician distribution. In this context, the estimation of carrier and channel parameters has been investigated in some earlier work by means of an algorithmic approach primarily based on heuristic considerations. In the current study, the authors will review the results obtained so far from a maximum‐likelihood (ML) point of view. A major output of the analysis is that the simple ad‐hoc framework achieved previously is indeed an ML solution, when the impairments introduced by Rician fading are spectrally flat and strictly band limited.